Migrasome and Tetraspanins in Vascular Homeostasis: Concept, Present, and Future - Zhang, Yaxing; Wang, Jing; Ding, Yungang; Zhang, Jiongshan; Xu, Yan; Xu, Jingting; Zheng, Shuhui; Yang, Hongzhi (Frontiers in Cell and Developmental Biology, 2020)
Cell migration plays a critical role in vascular homeostasis. Under noxious stimuli, endothelial cells (ECs) migration always contributes to vascular repair, while enhanced migration of vascular smooth muscle cells (VSMCs) will lead to pathological vascular remodeling. Moreover, vascular activities are involved in communication between ECs and VSMCs, between ECs and immune cells, et al. Recently, Yu Li et al. discovered a novel migration-dependent organelle “migrasome”, which mediated release of cytoplasmic contents, and this process was defined as “migracytosis”. The formation of migrasome is precisely regulated by tetraspanins (TSPANs) and cholesterol. Migrasomes can be taken up by neighboring cells, and migrasomes are distributed in many kinds of cells and tissues, such as in blood vessel, human serum, and in ischemic brain of human and mouse. In addition, the migrasome elements TSPANs are wildly expressed in cardiovascular system. Therefore, TSPANs, migrasomes and migracytosis might play essential roles in regulating vascular homeostasis. In this review, we will discuss the discovery, formation and distribution of migrasomes, the functions of migrasome elements TSPANs in vascular biology, and discuss the possible roles of migrasomes and migracytosis in vascular homeostasis.